2023
DOI: 10.1002/ca.23995
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on the trends of digital anatomy education

Abstract: Digital technologies are changing the landscape of anatomy education. To reveal the trend of digital anatomy education across medical science disciplines, searches were performed using PubMed, EMBASE, and MEDLINE bibliographic databases for research articles published from January 2010 to June 2021 (inclusive). The search was restricted to publications written in English language and to articles describing teaching tools in undergraduate and postgraduate anatomy and pre‐vocational clinical anatomy training cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 162 publications
0
3
0
Order By: Relevance
“…23,24 Despite the promising potential of digital carving activities, there continues to be some knowledge gaps in the literature. In light of some findings that such exercises have little value in improving students' knowledge or skills, 18,25 educators have stressed the need to conduct rigorous evaluation studies to examine the effectiveness of this teaching method. 3,9 Furthermore, research describing the design of digital carving tends to focus on the students' performance as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Despite the promising potential of digital carving activities, there continues to be some knowledge gaps in the literature. In light of some findings that such exercises have little value in improving students' knowledge or skills, 18,25 educators have stressed the need to conduct rigorous evaluation studies to examine the effectiveness of this teaching method. 3,9 Furthermore, research describing the design of digital carving tends to focus on the students' performance as the primary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…study programs [2,3]. In an extensive review conducted by Adnan and Xiao, which analyzed 156 research articles across six health disciplines, it was revealed that 35% of studies employed 3D digital printing tools, particularly in educational activities [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the fast development of digital anatomy technologies and the growing demand for digital literacies in higher education, there is a perceived need for educational strategies designed to promote the conceptualization and usefulness of human anatomy knowledge integrating digital literacies. Indeed, digital technologies such as augmented reality (AR), virtual reality (VR), video animations, and three‐dimensional (3D) reconstruction are increasingly adopted in topographic anatomy education in both lectures and practical classes (Wickramasinghe et al, 2022; Xiao & Adnan, 2022; Adnan & Xiao, 2023). Despite the significance of digital literacy in higher education, recent analyses suggest that digital and scientific skills embedded in current university curricula (De la Hoz et al, 2021) and health professional training programs (MacLure & Stewart, 2016) are largely insufficient and should be improved.…”
Section: Introductionmentioning
confidence: 99%